2014
DOI: 10.1093/ageing/afu101
|View full text |Cite
|
Sign up to set email alerts
|

The importance of detecting and managing comorbidities in people with dementia?

Abstract: CommentaryDementia is a debilitating condition characterised by global loss of cognitive and intellectual functioning, which gradually interferes with social and occupational performance. It is a common worldwide condition with a significant impact on society. There are currently 36 million people worldwide with Alzheimer's disease (AD) and other dementias [1]. This is expected to more than double by 2030 (65 million) and reach 115 million in 2050, unless a major breakthrough is made. The worldwide societal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…Comorbid conditions have been associated with dementia [48]; for instance, diabetes is associated with an increased rate of cognitive decline [49]. As discussed in the Results section, in the pcb-Cohort correlations with comorbidities were likewise evident, and there was a significant correlation with GID.…”
Section: Discussionmentioning
confidence: 81%
“…Comorbid conditions have been associated with dementia [48]; for instance, diabetes is associated with an increased rate of cognitive decline [49]. As discussed in the Results section, in the pcb-Cohort correlations with comorbidities were likewise evident, and there was a significant correlation with GID.…”
Section: Discussionmentioning
confidence: 81%
“…They highlight the need to develop effective interventions targeted to the particular needs of this population. Unique challenges exist in detecting and managing comorbidities for dementia patients [40], including difficulties in communicating medical complaints because of memory and language deficits. Clinical encounters may also be dominated by dealing with dementia and its manifestations, to the exclusion of other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that almost all (94%) nursing-home residents with dementia over a period of six weeks had changes to their health condition status, and many of the symptoms were considered treatable or reversible [25]. Early recognition and treatment of new conditions and exacerbations of ongoing conditions is thus of great importance [26]. It has been emphasized by assistant nurses that teamwork is a key component to engage people with dementia in activities, partly because of the opportunities to report and discuss their changing status [10].…”
Section: Discussionmentioning
confidence: 99%